Pemenuhan Hak Narapidana Hukuman Mati Dalam Program Pembinaan Kepribadian Bidang Kerohanian - Monica Astia Theresia Panjaitan; Budi Priyatmono; Umar Anwar; Ali Muhammad (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2026)
This research is motivated by the psychological condition of death penalty inmates facing severe pressures due to their sentence and uncertainty about execution timing. The main problem concerns how death-row inmates’ rights are fulfilled through spiritual guidance programs and the factors influencing this fulfillment at Gunung Sindur Special Class IIA Correctional Institution. A qualitative case study approach was used, involving in-depth interviews, participant observations, and document analysis. Findings indicate that death-row inmates fulfill their spiritual needs through the search for life meaning, inner peace, social connectedness, spiritual existence, and moral and ethical integrity. Despite psychological pressure, inmates managed to find meaning through religious activities. In conclusion, spiritual programs in the correctional facility positively impact the inmates’ psychological conditions. This research recommends strengthening spiritual development programs more intensively to support the emotional well-being of death-row inmates.